Decreased maternal hypothalamic-pituitary-adrenal axis activity in very severely obese pregnancy: Associations with birthweight and gestation at delivery. (January 2016) - Stirrat, Laura I.; O'Reilly, James R.; Barr, Sarah M.; Andrew, Ruth; Riley, Simon C.; Howie, Alexander F.; Bowman, Maria; Smith, Roger; Lewis, John G.; Denison, Fiona C.; Forbes, Shareen; Seckl, Jonathan R.; et al.
Highlights: Circulating maternal cortisol levels are lower in very severely obese pregnancy than in lean pregnancy. Other key hormones regulating pregnancy cortisol levels including CRH and CBG are lower in obese pregnancy. A lack of increase in urinary glucocorticoid clearance suggests a lesser activation of the HPAA in obese pregnancy. This may offer a novel mechanism underlying increased birth weight and longer gestation in obese pregnancy. Abstract: Background: The maternal hypothalamic-pituitary-adrenal-axis (HPAA) undergoes dramatic activation during pregnancy. Increased cortisol and corticotrophin-releasing-hormone (CRH) associate with low birthweight and preterm labor. In non-pregnant obesity, the HPAA is activated but circulating cortisol levels are normal or lower than in lean women. We hypothesized that maternal cortisol levels would be lower in obese pregnancy, and would associate with increased fetal size and length of gestation. Method: Fasting serum cortisol was measured at 16, 28 and 36 weeks gestation and at 3–6 months postpartum in 276 severely obese and 135 lean women. In a subset of obese ( n  = 20) and lean ( n  = 20) we measured CRH, hormones that regulate bioavailable cortisol (corticosteroid-binding-globulin, estradiol, estriol, and progesterone). Urinary glucocorticoid metabolites were measured in pregnant (obese n  = 6, lean n  = 5) and non-pregnant (obese n  = 7, lean n  = 7) subjects. Results: Maternal cortisol and HPAA hormones were lower in obese pregnancy. Total urinary glucocorticoid metabolites increased significantly in lean pregnancy, but not in obese. Lower maternal cortisol in obese tended to be associated with increased birthweight ( r  = −0.13, p  = 0.066). In obese, CRH at 28 weeks correlated inversely with gestational length ( r  = −0.49, p  = 0.04), and independently predicted gestational length after adjustment for confounding factors (mean decrease in CRH of −0.25 pmol/L (95% CI −0.45 to −0.043 pmol/L) per/day increase in gestation). Conclusion: In obese pregnancy, lower maternal cortisol without an increase in urinary glucocorticoid clearance may indicate a lesser activation of the HPAA than in lean pregnancy. This may offer a novel mechanism underlying increased birthweight and longer gestation in obese pregnancy.